WAHYU DAN ILMU PENGETAHUAN: Fungsi, Esensi dan Perbedaannya - Indah Lestari (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
Understanding life and predicting various natural and social events that will occur in human life requires science. Science is born through the process of reasoning. While the human mind has not been able to achieve supernatural things. Therefore, revelation is needed to guide reason, besides revelation also serves to strengthen the opinion of reason. Science and revelation are very important in human life because they both come from God. In Islam, the position of revelation is a source of knowledge that guides humans to be on the right path. Likewise, the position of science with various limitations, especially with current technological advances to help humans achieve their life goals. The point of difference between revelation and science is that the revelation of truth is absolute because it comes directly from God; while the science of truth is very relative because the source relies on ra'yu (reason, reason, ratio).